Improved characterisation of C2 and CH radical number density distributions in a DC arc jet used for diamond chemical vapour deposition - Rennick, C; Smith, A; Smith, J; Wills, J; Orr-Ewing, A; Ashfold, M; Mankelevich, Y; Suetin, N (2004)
Modelling studies of the plasma chemistry prevailing in CH4/H2/Ar mixtures in a DC arc jet reactor used for diamond chemical vapour deposition are reported, together with complementary new experimental data. Gas temperatures, Tgas, close to the substrate have been determined via analysis of the measured rotational state population distribution in C2(a) radicals and found to be ∼3200 K-similar to the temperature established previously in the free plume region. These, and previous (J. Appl. Phys. 92 (2002) 4213), Tgas and number density measurements are in good accord with the first results from a full 2D (r, z) modelling of the plasma chemical transformations and heat and mass transfer processes within the evolving plume and the periphery of the reaction chamber. The modelling shows formation of a shock front in the supersonic expansion, a few millimeters downstream from the nozzle exit. The spatial distributions of the various species number densities are predicted to display localised maxima and minima within the reaction chamber, reflecting the complex balance between gas flow, diffusive transfer and chemical transformations in the widely varying range of local conditions (notably Tgas and the H and H2 concentrations). The calculations provide clear evidence of the importance of gas flow re-circulation in transporting the hydrocarbon feedstock gas (methane) from the injection ring to the hot plume. C2H2, C2H, C, CH, C2 and C3 species are all predicted to be present at number densities > 5 × 1012 cm-3 in the plume incident on the substrate; it is suggested that all of the major C containing radical species (i.e. most notably C2H, C, CH, C2 and C3) must make some contribution to material growth in order to satisfy the experimentally measured film deposition rate. © 2003 Elsevier B.V. All rights reserved.